Cryoballoon pulmonary vein isolation in treating atrial fibrillation using different freeze protocols: The "ICE‐T 4 minutes vs 3 minutes" propensity‐matched study (Frankfurt ICE‐T 4 vs. 3). (18th June 2020) - Chen, Shaojie; Schmidt, Boris; Bordignon, Stefano; Tohoku, Shota; Urbanek, Lukas; Plank, Karin; Willems, Franziska; Throm, Christina; Konstantinou, Athanasios; Hilbert, Max; Zanchi, Simone; Bianchini, Lorenzo; et al.
Abstract: Background: Time‐to‐isolation (TTI) guided second‐generation cryoballoon (CB2) ablation has been shown to be effective for pulmonary vein isolation (PVI). Objective: The objective of this paper is to compare the safety and clinical outcome of CB2 PVI using the TTI guided 4 minutes vs 3 minutes freeze protocol. Methods: This was a propensity‐matched study based on an institutional database. Symptomatic atrial fibrillation (AF) patients who underwent CB2 PVI and systematic follow‐up were consecutively included. Results: A total of 573 patients were identified, of them 214 (107 matched‐pairs) symptomatic AF (paroxysmal AF: 61%, persistent AF: 39%) patients (age: 67.7 ± 11.2 years) were analyzed. The baseline characteristics were comparable between the two groups. Procedural time was significantly longer in the 4 minutes group compared to 3 minutes group (67.2 ± 21.8 vs 55.9 ± 16.9 minutes, P  < .0001). During a mean follow‐up of 2 years, the 4 minutes group was associated with a significantly higher rate of freedom from arrhythmia recurrence compared with the 3 minutes group (66.4% vs 56.1%, P  = .009), which was mainly driven by patients with persistent AF. The multivariate regression showed that the 4 minutes freeze was the independent predictor of freedom from arrhythmia recurrence. During the repeat procedure, the 4 minutes group was associated with a significantly higher rate of durable PVI. There was no difference regarding procedural adverse events between the two groups. Conclusion: As compared with the 3 minutes freeze, the TTI guided 4 minutes freeze is associated with a significantly higher rate of arrhythmia‐free and durable PVI without compromising the safety profile, patients with persistent AF may benefit from the TTI guided 4 minutes freeze more pronouncedly.